COMPARISON OF PAIN PERCEPTION BETWEEN INTRAVENA TRAMADOL INJECTION WITH PERIPROSTATIC LIDOCAINE INJECTION IN TRANSRECTAL ULTRASONOGRAPHY GUIDED PROSTATE BIOPSY PATIENT - Sawal, Zuhri; Djatisoesanto, Wahjoe; Djojodimedjo, Tarmono (Indonesian Journal of Urology, 2020)
Objective: To compare the pain perception between intravenous tramadol administration and PNB technique using lidocaine in TRUS guided prostate biopsy. Material & Methods: The design of this study is a prospective randomized clinical trial. The population of this study is BPH patients who will undergo TRUS guided prostate biopsy procedure according to the indication in our center. Randomization was done for the determination of groups 1 and 2. Group 1 was given tramadol injection 100 mg intravenously, while group 2 was given a local injection of lidocaine periprostatic. The Wong-Baker scale directly determined pain perception during the procedure. Results: The total samples in this study were 20 samples that met the inclusion and exclusion criteria with 10 samples in each group. The lidocaine group had a lower Wong Baker’s pain scale in both probe USG insertion and prostate biopsy than the tramadol group. However, it’s not statistically significant (p=0.089; p=0.125, respectively). Conclusion: The use of intravenous tramadol can be used as an alternative anesthetic/analgesic method in prostate biopsy patients. The pain scale of the intravenous tramadol can be compared with periprostatic lidocaine with lesser complications compared to periprostatic lidocaine.